Development of Small‐Molecule Trypanosoma brucei N‐Myristoyltransferase Inhibitors: Discovery and Optimisation of a Novel Binding Mode. Issue 11 (23rd September 2015) - Spinks, Daniel; Smith, Victoria; Thompson, Stephen; Robinson, David A.; Luksch, Torsten; Smith, Alasdair; Torrie, Leah S.; McElroy, Stuart; Stojanovski, Laste; Norval, Suzanne; Collie, Iain T.; Hallyburton, Irene; et al.
Abstract: The enzyme N ‐myristoyltransferase (NMT) from Trypanosoma brucei has been validated both chemically and biologically as a potential drug target for human African trypanosomiasis. We previously reported the development of some very potent compounds based around a pyrazole sulfonamide series, derived from a high‐throughput screen. Herein we describe work around thiazolidinone and benzomorpholine scaffolds that were also identified in the screen. An X‐ray crystal structure of the thiazolidinone hit in Leishmania major NMT showed the compound bound in the previously reported active site, utilising a novel binding mode. This provides potential for further optimisation. The benzomorpholinone was also found to bind in a similar region. Using an X‐ray crystallography/structure‐based design approach, the benzomorpholinone series was further optimised, increasing activity against T. brucei NMT by >1000‐fold. A series of trypanocidal compounds were identified with suitable in vitro DMPK properties, including CNS exposure for further development. Further work is required to increase selectivity over the human NMT isoform and activity against T. brucei . Abstract : HATs off to diversity ! Screening a diverse library against Trypanosoma brucei N ‐myristoyltransferase (NMT) identified hits based on thiazolidinone and benzomorpholine scaffolds. X‐ray crystallography of these compounds bound to Leishmania major NMT revealed novel active site binding conformations. Using the structural information, the benzomorpholine scaffold was optimised to a blood–brain barrier penetrant compound with activity against Tb NMT of <0.002 μm .